An Experimental Feasibility Study on Robotic Endonasal Telesurgery. Issue 4 (16th January 2015) - Wirz, Raul; Torres, Luis G.; Swaney, Philip J.; Gilbert, Hunter; Alterovitz, Ron; Webster, Robert J.; Weaver, Kyle D.; Russell, Paul T.
Abstract: BACKGROUND: Novel robots have recently been developed specifically for endonasal surgery. They can deliver several thin, tentacle-like surgical instruments through a single nostril. Among the many potential advantages of such a robotic system is the prospect of telesurgery over long distances. OBJECTIVE: To describe a phantom pituitary tumor removal done by a surgeon in Nashville, Tennessee, controlling a robot located approximately 800 km away in Chapel Hill, North Carolina, the first remote telesurgery experiment involving tentacle-like concentric tube manipulators. METHODS: A phantom pituitary tumor removal experiment was conducted twice, once locally and once remotely, with the robotic system. Robot commands and video were transmitted across the Internet. The latency of the system was evaluated quantitatively in both local and remote cases to determine the effect of the 800-km distance between the surgeon and robot. RESULTS: We measured a control and video latency of < 100 milliseconds in the remote case. Qualitatively, the surgeon was able to carry out the experiment easily and observed no discernable difference between the remote and local cases. CONCLUSION: Telesurgery over long distances is feasible with this robotic system. In the longer term, this may enable expert skull base surgeons to help many more patients by performing surgeries remotely over long distances.